The Repercussions of the Al-Abbasi Oppression on Al-Alawi Movement - Al-Kaabi, Rahim Sabah Baheen Mohammed; Al-Ahmadi, Qasim (Al-Adab Journal, 2022)
This title expresses the position of the Abbasids towards the Alawites, especially Ahl al-Bayt those of Infallibility and Purity - may peace be upon them - led in that by hidden hatred and detestable envy for what the pure progeny, peace be upon them, attained in divine status and stature. Godly, and therefore enmity, killing and violation, within a scheme that contains a lot of cunning and lack of fear of God Almighty, despite the fact that the success of their movement and the establishment of their state was based mainly on linking it to the Ahl al-Bayt, peace be upon them.The motive for choosing this topic: is to reveal the depth of the intellectual, social and political procedures, and analyze them on the basis of divine criteria.The problem in this research is:In the breadth, accuracy and sensitivity of the subject.The importance of the topic is centered on the statement of the reality of the Abbasid hostility towards Ahl al-Bayt, peace be upon him.The objectives of the research also aimed to show the extent of the crime of confrontation against the Alawites, and the backgrounds of that trend.The most prominent hypotheses of the research are the statement of hidden hatred and the personal and authoritarian motives that weave the threads of confrontation.The reality and the research community are the Abbasid state and its confrontation with Ahl al-Bayt, peace be upon him.We relied on a large number of sources, in addition to research and questions from history professors in the Hawza, as well as from previous studies on this subject.The most important results are the expansion of studies and research concerned with the intellectual, social and political life of Ahl al-Bayt, peace be upon him.I recommend studying history in depth and exposing the plots of the authoritarians against Ahl al-Bayt, peace be upon them.